The influence of corporate governance on water and sanitation state-owned companies sustainability indicator: the Brazilian case - Tardin, Isadora Gueiros Erthal (2022)
Studies that evaluate the efficiency of the provisions of service of the water and sanitation companies end up focusing only on the economic and operational dimensions. However, as they are public utilities that provide essential services to the population, there must be an assessment of their general impact on society. Thus, taking into consideration a global sustainability index of Brazil’s Regional Water and Sewage Providers (RWSPs), the present work attempts to find out whether high scores in good corporate governance characteristics are positively associated with a good sustainable outcome, which is supported by the results. This brings the approach of corporate governance criteria across the sanitation sector further into question.